THEORETICAL SUBSTANTIATION OF THE INTEGRITY PRINCIPLE IN THE PROFESSIONAL TRAINING SYSTEM FOR SOCIONOMIC SPECIALISTS (Psychology Travelogs, 2023)
The article highlights the considerations regarding the determinacy of the orientation of the modern system of professional training of socionomic specialists on the development of personality as an integral spiritual and moral entity, considering the importance, significance and complexity of solving professional tasks related to interpersonal interaction, psychological practice, rehabilitation support.The modern educational process of training specialists in socionomic sphere is characterised by a focus on the rational acquisition of knowledge for the purpose of further implementation in professional activities.  The current situation of Ukrainians is defined by treacherous aggression and a brutal war, cultural splits, the nation's desire to overcome post-Soviet spiritual degradation, blind idolatry, copying models of other cultures, lifestyles, and behaviours. That is why preserving the authentic integrity of a person through the development of the mind and heart, thinking and feelings, and the acquisition of fundamental knowledge for creative professional self-realisation is essential for professional education.The integrity ontogeny of a socionomic specialist's personality is considered as a set of quantitative and qualitative transformations that occur in the process of professional development and implementation. A specific form of embodiment of the dynamic integrity of a specialist's personality is the formation of a life strategy, which inherently manifests itself as a process of transition from the objectively possible to the objectively real, from the potential to the actual. The development of personality integrity in the process of professional development is based on the connection of its qualitatively different, changing states, and determining the productive direction of this process is the primary task of professional education.
Keywords: education; personality; self-realisation; integrity; dynamic integrity; development; transformation; specialist; professional development; socionomic sphere, transformation; self-development